Weld solidification cracking in a 304L stainless steel water tank. (September 2020) - James, M.N.; Matthews, L.; Hattingh, D.G.
Highlights: Solidification cracking example in austenitic stainless steel. Links the contribution of welding process and technique to the occurrence of hot cracking. Highlights the importance of attention to welding in avoiding hot cracking problems in industry. Shows the role of joint restraint and fit-up in the problem. Hot cracking occurred as micro-fissuring and gross interdendritic cracking. Abstract: Type 304L stainless steel alloy is known to be highly resistant to solidification cracking. In the present case the particular design of the welded seams in a simple 200 litre water tank, along with the likely manner in which the closing welds were made, has led to an interesting example of interdendritic hot cracking in 304L GTA welded using a 309L filler metal. The paper presents a short introduction to hot cracking in austenitic stainless steels and uses the fractographic evidence to demonstrate that this form of cracking has occurred. The cracking has occurred primarily from excessive residual restraint stresses arising from weld -fit-up and welding practice, combined with the particular sequence of welds made in finally closing the tank.